Interactive short films and online activities using the grow model to guide senior students - Suwansupa, Ingtawan; Wongdee, Prapassorn; Supinanont, Pakorn; Thamwipat, Kuntida (Humanities, Arts and Social Sciences Studies, 2024)
This research aimed: 1) to develop and evaluate the quality of interactive short films combined with online activities using the GROW Model to guide fourth-year students before entering internships, 2) to compare the perceptions of the sample group before and after viewing the media combined with online activities, and 3) to assess the satisfaction of the sample group towards the developed media and online activities using the GROW Model to guide fourth-year students before entering internships. Data were collected from undergraduate students enrolled in the ETM 363 Knowledge Management course during the first semester. A simple random sampling method was used, with a sample of 30 students. The statistics used included mean, standard deviation, and t-test. The research findings are as follows: The researchers developed 15-minute interactive short films combined with online activities using the GROW Model to guide fourth-year students before entering internships. Expert evaluation results indicated that the content quality of the media and activities was at a good level (X̅ = 4.32, S.D. = 0.38), and the quality of media presentation was at a good level (X̅ = 3.80, S.D. = 0.32). The perception results of the sample group showed that their perception after viewing the media combined with online activities using the GROW Model to guide fourth-year students before entering internships was significantly higher than before viewing, at the .05 statistical significance level. The satisfaction evaluation of the sample group towards the media and online activities was at a high level (X̅ = 4.34, S.D. = 0.50).